Evidence that low endocytic activity is not directly responsible for human serum resistance in the insect form of African trypanosomes - Natesan, S; Peacock, L; Leung, K; Gibson, W; Field, M (BioMed Central, 2010)
Background: In Trypanosoma brucei, the African trypanosome, endocytosis is developmentally regulated and substantially more active in all known mammalian infective stages. In both mammalian and insect stages endocytic activity is likely required for nutrient acquisition, but in bloodstream forms increased endocytosis is involved in recycling the variant surface glycoprotein and removing host immune factors from the surface. However, a rationale for low endocytic activity in insect stages has not been explored. Here we asked if endocytic down-regulation in the procyclic form was associated with resistance to innate trypanolytic immune factors in the blood meal or tsetse fly midgut. Findings: Using a well-characterized procyclic parasite with augmented endocytic flux mediated via TbRab5A overexpression, we found that insect stage parasites were able to grow both in the presence of trypanosome lytic factor (TLF) provided in human serum, and also in tsetse flies. Additionally, by placing blood stage parasites in restricted glucose medium, we observed that enlargement of the flagellar pocket, a key morphology associated with defective endocytosis, manifests in parallel with loss of cellular ATP levels. Conclusions: These observations suggest that a high rate of endocytosis per se is insufficient to render insect form parasites sensitive to TLF or tsetse-derived trypanocidal factors. However, the data do suggest that endocytosis is energetically burdensome, as endocytic activity is rapidly compromised on energy depletion in bloodstream stages. Hence an important aspect of endocytic modulation in the nutrient-poor tsetse midgut is likely energetic conservation.